Recommendations for Sustainable Ancient DNA Research in the Global South: Voices From a New Generation of Paleogenomicists - Ávila-Arcos, Maria C.; de la Fuente Castro, Constanza; Nieves-Colón, Maria A.; Raghavan, Maanasa (Frontiers in Genetics, 2022)
Paleogenomics - the study of ancient genomes - has contributed significantly to our understanding of the evolutionary history of humans, facilitated by improved methods for the recovery and analysis of ancient DNA. The popularization of paleogenomics in the media coupled with publications in “high impact” journals has driven the amassing of ancestral human remains from global collections, often with limited to no engagement or involvement of local researchers and communities. This practice has led to limited representation of researchers from the Global South at the research design and subsequent stages. Additionally, Indigenous and descendant communities are often alienated from popular and academic narratives that both involve and impact them, sometimes adversely. While some countries have safeguards against ‘helicopter science’, such as federally regulated measures to protect their biocultural heritage, others have variable oversight of destructive sampling and exportation of human remains, and differing requirements for accountability or consultation with local researchers and communities. These stark contrasts and gaps in regional policies lend themselves to persistent colonial practices. While essential critiques and conversations in this sphere are taking place, these are primarily guided through the lens of US-based heritage legislation such as the Native American Graves and Protection Act. Here, we expand the conversational scope by accounting for diverse regional contexts and challenges, drawing from our own research experiences in paleogenomics. True collaborations involve knowledge sharing, capacity building, mutual respect, and equitable participation, which require time and the implementation of sustainable research methods; amass-and-publish strategy is simply incompatible with this ethos.